The Influence of Safety in Design Implementation on Construction Safety Performance in Building Projects - Enos Frendly Lase; Indri Santiasih; Abu Jami’in (International Journal of Marine Engineering Innovation and Research, 2025)
The construction industry is one of the sectors with the highest occupational accident rates, particularly during the project execution phase. To address this issue, the concept of Safety in Design (SiD) has been introduced as a proactive approach to integrate hazard identification and risk mitigation into the design phase of construction projects. This study aims to analyze the influence of Safety in Design implementation on improving construction safety performance in building projects within DKI Jakarta. The research employs a quantitative method using a survey approach with 50 respondents representing project management roles from four high-rise building projects managed by a state-owned enterprise. The variables evaluated in this study include human/engineer factors, management aspects, and compliance and technology systems. Data were analyzed using ordinal logistic regression with several statistical tests, such as the Wald test, goodness-of-fit test, and test of parallel lines. The findings indicate that all SiD-related factors significantly contribute to enhancing construction safety performance. Among these, the management aspect exhibits the most dominant effect, followed by technology and compliance, and human factors. The model demonstrates good fit and validity, confirming the relevance of incorporating safety considerations at the early project planning stage. These results highlight the strategic importance of empowering designers and project managers with safety-oriented knowledge and integrating risk-based decision-making in the design process to reduce occupational accidents and improve safety outcomes in the field